2016
DOI: 10.3354/meps11728
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic distribution of the eel Anguilla luzonensis: dependence upon larval duration and oceanic currents

Abstract: Anguilla luzonensis, a recently identified tropical Anguilla species, was categorized as 'Near Threatened' in the International Union for Conservation of Nature (IUCN) Red List in 2014. However, its biogeographic distribution and dispersal mechanism remain unconfirmed. This study aimed to clarify the biotic and abiotic factors that may shape the eel's dispersal range, which could help to establish suitable conservation strategies. Glass eel distribution was investigated in Taiwan, Luzon, Mindanao, and Sulawesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…If true, this species has a unique larval 0°20°W 40°W 60°W 80°W 10°E 0°20°W 40°W 60°W 80°W dispersal and recruitment pattern compared with both A. japonica and A. marmorata because it appears to have a very narrow species range centered on the northern Philippines according the lack of its detection in other areas in studies using genetic identification of specimens (e.g., Kuroki et al 2014;Han et al 2016). The sampling surveys conducted in the northern Indonesian Seas region have indicated that anguillid leptocephali are usually present but not at high abundances.…”
Section: Distribution and Dispersal Of Anguillid Larvaementioning
confidence: 99%
“…If true, this species has a unique larval 0°20°W 40°W 60°W 80°W 10°E 0°20°W 40°W 60°W 80°W dispersal and recruitment pattern compared with both A. japonica and A. marmorata because it appears to have a very narrow species range centered on the northern Philippines according the lack of its detection in other areas in studies using genetic identification of specimens (e.g., Kuroki et al 2014;Han et al 2016). The sampling surveys conducted in the northern Indonesian Seas region have indicated that anguillid leptocephali are usually present but not at high abundances.…”
Section: Distribution and Dispersal Of Anguillid Larvaementioning
confidence: 99%
“…Therefore, metamorphosis at a younger age results in migration to lower latitudinal growth habitats. This mechanism could also explain the difference in biogeographic distribution between the A. japonica and Anguilla luzonensis Watanabe, Aoyama & Tsukamoto 2009, individuals of which are spawned in the vicinity of A. japonica and are also transported with the NEC and Kuroshio Current (Han et al, ). Unlike A. japonica , which is distributed widely across East Asia, A. luzonensis tends to be concentrated in the southernmost part of East Asia around Luzon Island due to its short and narrow range of larval duration (Han et al, ).…”
Section: Distribution and Habitat Of Metamorphosing Leptocephalimentioning
confidence: 99%
“…This mechanism could also explain the difference in biogeographic distribution between the A. japonica and Anguilla luzonensis Watanabe, Aoyama & Tsukamoto 2009, individuals of which are spawned in the vicinity of A. japonica and are also transported with the NEC and Kuroshio Current (Han et al, ). Unlike A. japonica , which is distributed widely across East Asia, A. luzonensis tends to be concentrated in the southernmost part of East Asia around Luzon Island due to its short and narrow range of larval duration (Han et al, ). Similarly, although the leptocephalus distribution and spawning area of Anguilla marmorata Quoy & Gaimard 1824 overlap with those of the A. japonica (Miller et al, ; Kuroki et al, ), there are latitudinal differences in their growth habitats, probably due to differences in their larval durations (Leander et al ., ).…”
Section: Distribution and Habitat Of Metamorphosing Leptocephalimentioning
confidence: 99%
“…The spawning occurred through the whole year in several tropical eel species ( Arai et al., 2001 ; Shiao et al., 2002 ; Arai et al., 2016 ; Arai and Abdul Kadir, 2017a ). The year-round spawning together with constant early growth during the oceanic period throughout the year, expand the recruitment period to continental habitats throughout the entire year for tropical anguillid eels ( Beumer and Sloane, 1990 ; Arai et al., 1999b ; Sugeha et al., 2001 ; Han et al., 2012b , 2016a ; Leander et al., 2012 ; Aoyama et al., 2015 ; Hewavitharane et al., 2018 ). The continuous spawning migration may stimulate breeding with different cohorts (year classes) or divergent habitats within the population.…”
Section: Evolution Of Oceanic Migrationmentioning
confidence: 99%
“…The lengthy duration of the larval stage might lead to global dispersion and their consequent speciation. The durations of leptocephalus stages span from several months to approximately two years (e.g., Tsukamoto, 1990 ; Lecomte-Finiger, 1992 ; Cheng and Tzeng, 1996 ; Arai et al., 1999a , 2001 ; 2003a ; Wang and Tzeng, 2000 ; Marui et al., 2001 ; Robinet et al., 2003a ; Robinet et al., 2008 ; RĂ©veillac et al., 2008 , 2009 ; Bonhommeau et al., 2010 ; Han et al., 2016a , 2019 ; Hewavitharane et al., 2020 ). Many marine organisms have a planktonic larval stage during their early life and larvae are passively transported by oceanic currents.…”
Section: Introductionmentioning
confidence: 99%